Pengaruh Fomo (Fear of Missing Out), Gaya Hidup, dan Persepsi Harga Terhadap Impulsive Buying Live Streaming Shopee pada Generasi Zilenial di Kota Pekanbaru - Diana Asadillah; Ulfiah Novita (Yayasan Almanar Pujud, 2026)
The development of digital technology has changed people's consumption patterns, especially among Generation Z (Zilennials). E-commerce platforms such as Shopee, with its live streaming feature, have created an impulsive buying phenomenon driven by psychological and social factors. This study aims to examine the influence of FOMO (Fear of Missing Out), Lifestyle, and Price Perception on Impulsive Buying behavior on Shopee's live streaming feature. The study was conducted in Pekanbaru City and targeted Ziennials who actively shop through Shopee Live. The results showed that partially, the FOMO and Lifestyle variables were proven to have a positive and significant effect on Impulsive Buying. Meanwhile, Price Perception did not show a significant effect partially. However, the three independent variables were simultaneously proven to have a significant effect on Impulsive Buying. These findings indicate that in the context of live streaming, impulsive buying decisions among Ziennials are more strongly driven by social anxiety (FOMO) and a consumptive lifestyle, rather than rational considerations regarding price.